All New "D CITI RAT": Inovasi, Revitalisasi dan Pengadaan Pada "D CITI RAT" - Arifin, Ryan; Kurniawan, Jefri; Rheza, Muhammad (Program Kreativitas Mahasiswa - Kewirausahaan, 2014)
Background: The need for white rats and mice for animal research trials has increased in West Borneo that required innovation in terms of addition of white rats and mice variant strains to fulfiling the needs of students, lecturers, and researchers for experimental animals. Objective: To increase production of white rats and mice as well as new innovations on the DCITI RAT husbandry to fulfiling the needs of experimental animals in West Borneo. Method: This business named âAll New D CITI RATâ, that developed and innovated from existing business that named D CITI RAT (Dagangan Tikus Putih dan Mencit Untuk Keperluan Skripsi dan Riset) in terms of production methods to increase variants of white rats and mice to provide conditioned mice for research (hipercholesterolemia, diabetic rats, etc) and production placerenovation to meet the standards of research mice according to WHO. Results: D CITI RAT business offered 4 products that are Wistar rats, Sprague Dawley strain and strain Swiss Webster mice and Balb/C. Conclusion: D CITI RAT businesshas been done very well and produce satisfactory results during the period, proved by the number of sales that exceeded expectations. Keywords : All New âDâ Citi Ratâ, Innovation, Revitalitation, Procurement.